Pengaruh Succession Planning, Transformational Leadership, Training Satisfaction Terhadap Turnover Intention Karyawan Pada Sektor Publik Kementerian Agama Jakarta Pusat - Amelia Wanggi; Mutiara Panggabean; Tiara Puspa (Esensi: Jurnal Bisnis dan Manajemen, 2019)
This study tries to analyze the effect of succession planning, transformational leadership, training satisfaction on employee turnover intention in the public sector of the Central Jakarta Ministry of Religion. Responding to this study, an experiment of 120 respondents from the Central Jakarta Ministry of Religion staffing company. The sampling method uses purposive sampling and uses descriptive statistical data analysis methods (average) and multiple regression analysis. In this research, succession planning, transformational leadership, and training satisfaction, were obtained negatively towards company turnover intention in the public sector, especially succession planning. From the results of this study, it was agreed by the leadership of the company to pay more attention to succession planning or management of employee talents, allow and add training and coaching for future leaders to be more transformational to provide beneficial investments in terms of employee career development.